Ancaman Non-Tradisional dalam Keamanan Maritim: Studi Kasus Perompakan di Perairan Asia Tenggara - Muh. Ibnu Bintang (Indonesian Maritime Researchers and Lecturers, 2025)
Sea armed robbery is one of the growing non-traditional threats that has a significant impact on maritime security in Southeast Asia. This study aims to examine the dynamics of sea armed robbery in the Southeast Asian region and analyze regional efforts through various multilateral and bilateral cooperation mechanisms. The method used in this research is a qualitative study with a descriptive-analytical approach. There are countermeasures through forums such as the ASEAN Maritime Forum (AMF), ASEAN Coast Guard Forum (ACGF), and the ReCAAP agreement in reducing piracy incidents. However, these efforts still face challenges. Therefore, it is necessary to strengthen institutional capacity, harmonize policies, and increase trust and collaboration between countries to form a regional maritime security system that is more resilient and adaptive to dynamic threats.